Balanços de momentos estatísticos de segunda ordem na camada limite atmosférica diurna e noturna em função do vento - Pozzobon, Alessandro Eugenio Denardin (2021)
The study presents an observational analysis of the terms in the budgets of three planetary boundary-layer second-order statistical moments: turbulent kinetic energy (TKE), heat flux and temperature variance. These have been chosen because they are commonly employed in weather and climate numerical weather forecast schemes. The analysis is done using 172 days and nights of observations carried out at a 30 m micrometeorological tower in southern Brazil, at the campus of Universidade Federal de Santa Maria. Four levels of observations with threedimensional sonic anemometers, deployed at heights of 3, 6, 14 and 30 m form the surface, are used. The analysis is split between daytime (convective) and nighttime (stable) periods. In both cases, the budget terms are considered in terms of the mean wind speed near the surface and of the stability parameter from Monin-Obukhov similarity theory. The terms presented are those of shear production, buoyant production/destruction and dissipation in the TKE budget, thermal gradient production and buoyant production/destruction in the heat flux budget, thermal gradient production and dissipation in the temperature variance budget as well as the turbulent transport terms in the three budgets. Horizontal transport terms and those associated with pressure perturbations have not been observed. At daytime, TKE budget is dominated by shear and buoyant production, while dissipation is the dominant destruction mechanism. The tke budget residual indicates that the transport by pressure perturbations is positive near the surface. At night, shear production and dissipation dominate the budget, while buoyant destruction is smaller, albeit physically relevant. The turbulent transport term switches sign according with the turbulence regime. The diurnal heat flux budget, the dominant term may be either the thermal gradient or buoyant production, depending on the wind speed or stability parameter, while at night they have opposite signs and dominate the budget. Regardless of the period, the temperature variance budget displays a near-equilibrium between thermal gradient production and dissipation. The main aim of the dissertation is to identify the dominant terms in the budgets and their dependence on the mean wind speed and stability.